On the Legal Case as Drawing - Condello, Angela (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
In this essay, I analyse the legal case through an analogy with drawing. In the first place, this analogy is described at the level of the basic characters of both drawing and case; then, the analogy is approached from a dynamic perspective, with a focus on the performative nature both of the act of drawing and of the act of judging on the singular legal case. The first section prepares the argumentative foundations for the following section (§2), dedicated to a brief comparison between two perspectives rooted in social ontology, i.e. Searle’s intentionality and Ferraris’ documentality. Through their comparison, and with an eye at their integration, the analogy behind the whole essay drives to develop some remarks around the nature of the law (§3). By bringing back the focus on the line both uniting and dividing abstraction and concreteness, facts and norms, the legal case and the allegory of drawing lead to reflect on law as a progression of singular cases and as a continuous process of reciprocal integration between the individual and the universal. Parole chiave: Drawing; Legal case; Singularity; Intentionality; Documentality Indice: 1. L’allegoria del disegno applicata al caso giuridico – 2. Il disegno e il giudizio come atti performativi – 2.1 Il caso giuridico come progetto: tra intenzione e traccia – 3. Il diritto come integrazione reciproca dell’individuale nell’universale – Riferimenti bibliografici